Alopecia Areata: Complex Roots and Potential Cures - Vidit Deshpande; Kedar P. Navsariwala; Atharva Shinde1; Adri Raj Saha; Navyansh Asthana (International Journal of Vaccines, 2024)
Autoimmunity is when the healthy organs of an individual’s body are attacked by its own immune system, leading to illness or functional abnormalities. The hair follicles (HFs) are wrongly destroyed by the immune system in a condition known as Alopecia Areata and results in chronic non-cicatricial hair loss discernible by spherical patches. It’s a severely worsening or relapsing malady that can be permanent during severe falling out of hair. In 'Alopecia areata', the phenomenon of lymphocytic penetration is also detected during the 'anagen phase' of proliferating HFs. The ‘JAK-STAT’ pathway is a critical factor that carries out the coordination of the self-inflammatory system ('Immune system'), helps in polarizing ‘T-helper cells’, and carries out multiple functions via several transmembrane receptor families. A major participant in alopecia areata is the infiltrating interferons 'IFN-γ' and the 'TNF-α' in the HF. This compensates HF’s immunity and upregulates the expression of MHC-I. Importantly, the SOCS-3 protein exercises a major part in preventing CD8+ T cell maturation and IFNγ signaling. Immunoglobulin-G (IgG) also appears prevalent in AA victims. The objective covered in the review article is to converse about the diverse immunological, molecular, therapeutic elements in addition to the clinical assessments and their findings that result in loss of hair in AA subjects.
Keywords: Alopecia areata; Autoimmunity; Hair loss; JAK-STAT; SOCS-3